Analytical fault tree and diagnostic aids for the preservation of historical steel truss bridges. (March 2022) - Sangiorgio, Valentino; Nettis, Andrea; Uva, Giuseppina; Pellegrino, Francesco; Varum, Humberto; Adam, Jose M.
Highlights: The problem of historical steel truss bridges preservation is presented. A novel hybrid deductive failure analysis approach (Analytical Fault Tree - AFT) is developed. Numerical models investigate fault scenarios including fatigue and concurring causes. AFT and fault scenarios are applied to a historical bridge located in the East of Spain. Guidelines and conservation strategies are obtained for the investigated bridge. Abstract: Historical steel bridges represent an important construction typology integrating the constructive heritage of the past century that needs to be preserved. Exposure to fatigue phenomenon, aging, improper design or execution, extreme events, and other aggressive environmental agents can seriously compromise the conservation and performance of these structures as some recent catastrophic collapses have shown (Mississippi River bridge, Minneapolis, Minnesota 2007; Kinzua Bridge State Park, Pennsylvania 2003). In this context, the diagnostic of historical steel bridges becomes of basic importance to identify and implement maintenance, monitoring and conservation strategies. Fault Trees are useful tools for practitioners that provide a complete overview of possible failures. In the related literature, this instrument is mainly applied with approaches that are based on previous experience or failures detected in similar structures, and so the Fault Tree can only provide qualitative support. This paper proposes a new method to achieve an "Analytical" Bridge Fault Tree linking the technician's experience and the numerical simulations of different fault scenarios. The latter are achieved by a numerical model able to consider fatigue failure and different concurring causes in the analysis (e.g., and aggressive phenomena, corrosion, defects, lack of maintenance). The proposed approach was applied to a historical railway steel truss bridge located in the East of Spain (Valencia Region) in order to show its applicability and potential.